Epidemiological study on non-drug-resistant Acinetobacter - Yan, Linsheng; Mohd Zaki Mohd Zaili; Shu, Meng Goh; Jualang Azlan Gansau; Poh, Lucky Wah Goh (Amaltea Medical Publishing House (AMPH), Bucharest, Romania, 2024)
To explore the prevalence of non-drug-resistant Acinetobacter, in order to provide a theoretical basis for clinical anti-infection treatment of non-drug-resistant Acinetobacter. The medical records of inpatients in various departments of the hospital were retrospectively sorted out, and the data covered many aspects of the human body such as blood, saliva, sputum and tissue. Immediately after collection, samples were labeled and stored in a refrigerator at 8°C to investigate clinical distribution and prevalence. Among the 158 strains of non-drug-resistant A. baumannii, 30 strains were obtained from sputum samples (18.98%). The second most common type was 11 strains in urine (6.96%); 44 blood samples, accounting for 27.85%. The age distribution was as follows: 8 strains (11.39%) were minors under 18 years of age; there were 20 strains (12.66%) aged from 18 to 30 years old; 75 strains (47.47%) were over 60 years old. Nine of the 158 non-resistant strains were included, accounting for the highest proportion of A. Boumani, followed by A. Boumani Hospital and A. Boumani Pittsburgh. At present, the bacterial strain is mostly detected in blood samples, and is mainly distributed in middle-aged and old patients over 50 years old, and is relatively popular in ICU and FMW departments. The drug-resistant A. baumannii in hospital specimens tends to accumulate in ICU, and the nosocomial infection caused by this disease is mainly concentrated in the elderly and patients with various basic diseases, with a high detection rate. Acinetobacter strains are generally resistant, and polymyxin B and minocycline are often the first choice of therapy.